Living with History, 1914-1964 Rebuilding Europe after the First and Second World Wars and the Role of Heritage Preservation / La reconstruction en Europe après la Première et la Seconde Guerre Mondiale et le rôle de la conservation des monuments historiques - Bullock, Nicholas; Verpoest, Luc (2021)
Living with History focuses on a particular aspect of heritage preservation in the 20th century: destruction and post-war reconstruction in Belgium, France, Germany, Great Britain, and The Netherlands.This book establishes a status quaestionis for the historiography of wartime and post-war preservation, and sets these particular developments in preservation history in the context of the general evolution of architecture and urbanism. It studies the specific role of conservationists and heritage institutions and administrations in the overall reconstruction, and examines the specific role of architects and planners in preservation matters.Living with History se concentre sur un aspect particulier de la conservation du patrimoine au XXe siècle : les destructions et la reconstruction d' après-guerre en Belgique, en France, en Allemagne, en Grande-Bretagne et aux Pays-Bas.Cet ouvrage dresse un état de la question sous l' angle de l' évolution d' ensemble de l' architecture et de l' urbanisme. Il étudie le rôle des conservateurs et des institutions patrimoniales dans la reconstruction en général et examine le rôle spécifique des architectes et urbanistes dans les domaines liés à la conservation.